2021
DOI: 10.1101/2021.07.22.21260852
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparison of infected and vaccinated transplant recipients highlights the role of Tfh and neutralizing IgG in COVID-19 protection

Abstract: Transplant recipients, which receive therapeutic immunosuppression to prevent graft rejection, are characterized by high COVID-19-related mortality and defective response to vaccines. Having observed that previous infection by SARS-CoV-2 but not the standard 2 doses scheme of vaccination, provided complete protection against COVID-19 to transplant recipients, we undertook this translational study to compare the cellular and humoral immune responses of these 2 groups of patients. Neutralizing anti-Receptor Bind… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 47 publications
1
12
0
Order By: Relevance
“…In the present study, we observed that the seroconversion rate with Covishield and Covaxin is comparable, or relatively higher, to that of the mRNA-based vaccines. Infection with SARS-CoV-2 usually triggers the generation of high titers of protective neutralizing anti-spike IgGs in RTRs, similar to our observations [ 22 ]. A study also revealed that the main predictor of successful seroconversion after vaccination is a previous history of COVID-19 in RTRs.…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, we observed that the seroconversion rate with Covishield and Covaxin is comparable, or relatively higher, to that of the mRNA-based vaccines. Infection with SARS-CoV-2 usually triggers the generation of high titers of protective neutralizing anti-spike IgGs in RTRs, similar to our observations [ 22 ]. A study also revealed that the main predictor of successful seroconversion after vaccination is a previous history of COVID-19 in RTRs.…”
Section: Discussionsupporting
confidence: 90%
“…However, only 25% (range: 2.5%–48%) of KTRs develop adequate antibody response after the “standard” two doses of COVID‐19 mRNA vaccine 6‐14 . These antibodies are responsible for the neutralization of the virus, that can be assessed using in vitro functional assay, which currently represents the best available correlate of protection against severe COVID‐19 for both the general population 15 and KTRs 16 . Accordingly the lack of adequate antibody response after vaccination in KTRs correlated with the occurrence of (sometime severe forms of) COVID‐19 in vaccinated patients 17‐19 …”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13][14] These antibodies are responsible for the neutralization of the virus, that can be assessed using in vitro functional assay, which currently represents the best available correlate of protection against severe COVID-19 for both the general population 15 and KTRs. 16 Accordingly the lack of adequate antibody response after vaccination in KTRs correlated with the occurrence of (sometime severe forms of) COVID-19 in vaccinated patients. [17][18][19] Preliminary reports suggest that a third dose (D3) of vaccine improves the humoral response in transplant recipients.…”
mentioning
confidence: 98%
“…This vulnerable population has therefore been prioritized for vaccination. However, after the "standard" 2 doses of mRNA vaccine only few KTRs develop appropriate levels of anti-receptor binding domain of spike protein (RBD) IgG [6][7][8] , which are responsible for the neutralization of the virus and the protection against COVID-19 9 . Accordingly, we and others have reported cases of vaccinated KTRs with (sometime severe forms of) COVID-19 10,11 .…”
Section: Introductionmentioning
confidence: 99%